"Long-term follow-up and prognosis of celiac hepatitis". Issue 12 (23rd September 2022) - Garrido, Isabel; Liberal, Rodrigo; Peixoto, Armando; Macedo, Guilherme
Abstract : Introduction: Celiac disease has been associated with abnormal liver function tests at diagnosis that usually resolve with a gluten-free diet (GFD). The aim of this study was to assess the evolution of liver involvement and possible long-term complications in patients on a GFD. Methods: Retrospective and single-center study, which included all individuals with Celiac disease followed in specialized consultation in a tertiary referral hospital. Results: A total of 162 patients were included, most of them female (77.8%) with a median age of 24 years (IQR, 7–39). Seventy-four (45.7%) patients had abnormal liver function tests at diagnosis. These individuals had higher anti-tissue transglutaminase IgA (tTG-IgA) antibody titers (126 vs. 29 IU/L; P = 0.003). There were no significant differences in the Marsh classification ( P = 0.599). During follow-up, most celiac hepatitis patients had normalization of liver function tests and tTG-IgA antibodies. At the last follow-up, all the patients had fibrosis-4 index <2.4 and an aspartate aminotransferase-to-platelet ratio index score <0.6. Vibration-controlled transient elastography showed values <6.4 kPa in all cases. On the other hand, it was found that 42.9% of the individuals had a controlled attenuation parameter >206.5 db/m. Conclusions: In our cohort, liver function tests normalized in the vast majority of celiac hepatitis patients on a GFD, with no progression to chronic liver disease. It should be noted the high number of individuals who present hepatic steatosis during follow-up, which may be related to a diet that tends to be hyperlipidemic and hypercaloric.